6•(x+8)+8•(x-6)=-126
Răspunsuri la întrebare
Răspuns de
2
Răspuns:
x=9
Explicație pas cu pas:
6•(x+8)+8•(x-6)=-126
6x+48+8x-48=126
14x=126
x=126÷14
x=9
Proba:
6·(9+8)+8·(9-6)=6·17+8·3=102+24=126
Răspuns de
2
Explicație pas cu pas:
6x+48+8x-48=126
14x=126+48-48
x=9
Alte întrebări interesante
Engleza,
8 ani în urmă
Engleza,
8 ani în urmă
Ed. tehnologică,
8 ani în urmă
Limba română,
8 ani în urmă
Biologie,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă